Case report: Complete response in TMB-H advanced uterine clear cell carcinoma: a case analysis of paclitaxel albumin-bound combined with PD-1/CTLA-4 bispecific antibody - Chen, Yue; Zhou, Wenting; Wang, Yili (Frontiers in Immunology, 2024)
BackgroundUterine clear cell carcinoma (UCCC) is a rare and aggressive subtype of endometrial cancer, often presenting at an advanced stage with poor prognosis. Treatment options for advanced or recurrent UCCC are currently limited, especially after platinum-based chemotherapy has failed.Case presentationWe present the case of a 49-year-old female diagnosed with stage IV uterine clear cell carcinoma. The patient had a history of atrial fibrillation and initially received several surgical interventions and platinum-based chemotherapy, but these treatments resulted in poor outcomes and rapid tumor progression. Genetic testing showed a high tumor mutation burden (TMB-H, 42.24 mutations/Mb) with stable microsatellites and a suspected harmful mutation in the PMS2 gene. After conventional therapies failed, the patient received a combination treatment of cadonilimab (375 mg) and albumin-bound paclitaxel (380 mg) for six cycles. This was followed by cadonilimab monotherapy for maintenance. This treatment regimen led to a complete response (CR), with no detectable abdominal fluid or enlarged lymph nodes by January 4, 2023. The CR status was maintained during a follow-up on April 07, 2024. The adverse effects included severe myelosuppression, mild skin reactions, hypothyroidism, and Grade 3 hyperglycemia, all of which were managed symptomatically.ConclusionThis case illustrates how effective AK104/Cadonilimab (a PD-1/CTLA-4 bispecific) can be when combined with albumin-bound paclitaxel for treating advanced UCCC, especially in patients who have not responded to standard therapies. The patient’s complete and lasting response shows the potential of PD-1/CTLA-4 bispecific immunotherapy. This suggests that cadonilimab could provide important clinical benefits for patients with advanced or recurrent UCCC.